Pelatihan Dasar Animasi Dengan Flash Untuk Guru Dan Staff Sekolah Sds As Salam- Pamulang - Simon Simarmata; Tedi Purwanto (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The use of technology today is needed, especially by humans, where technology is the entire means to provide goods needed for the survival and comfort of human life. The era that is growing rapidly apart from being supported by sophisticated equipment cannot be separated from the role of humans in its use. Humans as human resources in addition to creating technology must also be able to use it. The technology of the future will gradually replace the role of humans if the person is not sensitive to its development.This development, if realized, touches almost all aspects such as education, banking, health, manufacturing, construction and planning as well as several other industries. The use of technology in education has a very clear role. Today's knowledge is not only obtained in printed form or viewing sources through books in printed form because apart from requiring time, money and a place to find it, it is not easy. With existing technology, quality improvement can be done through applications, both original and man-made, that have or do not have copyright. The current education industry, both teachers and students, must understand technology. Developing the knowledge and abilities of every human being can be done by self-study or by attending trainings. As Salam SDS School, one of which is located in the South Tangerang area, participated in training to create animated text and images using the Macromedia Flash application for teachers and staff at the school. The training was carried out with the enthusiasm of the teachers and their staff for a full day with quite careful planning through community service by Pamulang University.